2009
DOI: 10.1097/jnr.0b013e3181c15a38
|View full text |Cite
|
Sign up to set email alerts
|

A Tailored Web-Based Intervention to Promote Women's Perceptions of and Intentions for Mammography

Abstract: Results of the study validated the importance of utilizing theory for tailored intervention design to enhance individuals' positive perceptions of health behaviors. Additional studies should consider the effect of various processes and activities on women at different stages of acceptance of the need to obtain a mammogram to further determine outcomes and apply such to mammography screening behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Due to the nature of the intervention (stretching), blinding was not possible in this trial. For the remaining nine trials with adequate follow-up, 17 23 30 38 42 43 46 48 51 we were unable to conclude how methodologically sound these trials were, due to poor reporting.…”
Section: Sources Of Internal Bias: Overallmentioning
confidence: 73%
“…Due to the nature of the intervention (stretching), blinding was not possible in this trial. For the remaining nine trials with adequate follow-up, 17 23 30 38 42 43 46 48 51 we were unable to conclude how methodologically sound these trials were, due to poor reporting.…”
Section: Sources Of Internal Bias: Overallmentioning
confidence: 73%
“…At the planning stage of the interventions, researchers need to consider developing step-by-step details on intervention implementation (eg, how many times the participant will be required to visit the Web site). 39,58 For example, in the study by Whittemore et al, 58 the researchers identified the patterns of their Web site usages by counting the number of participant log-ins and the number of sessions that the participants navigated and used/completed.…”
Section: Logistics For Usersmentioning
confidence: 99%
“…The target populations of the Web-based interventions in the literature included women, adults, and college students. [39][40][41][42][43] A quarter of the Web-based interventions were aimed at women, 39 about a quarter of the interventions aimed at adults, 3,40,43 and approximately 12% of them aimed at college students. 42 In the WPAPP study, the target population was Korean American midlife women, who were chosen because (1) Korean Americans represented one of the largest subethnic groups that we recruited in our previous studies; (2) they are the most rapidly growing group in the US 44 ; (3) the research team had extensive experience with this group in previous studies; (4) they are culturally homogeneous group that has rarely interbred with other groups until recently 22 ; and (5) Koreans are one of the ethnic minority groups who use the Internet more than any other.…”
Section: Target Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend was observed while analyzing the concordance for each of the health behaviors, thus ensuring content validity aimed at both the TTM and the recommendations of health in Mexico. The questionnaire offers health professionals in Mexico the option to apply a fast, simple, and innovative screening test, to identify persons who may benefit from interventions to promote health behaviors, and at the same time they can count on intervention strategies delimited to the stage of change 6,811,23…”
Section: Conclusion/implications For Practicementioning
confidence: 99%